Temperature Rise Induced by Light Curing Unit Can Shorten Enamel Acid-Etching Time - Ahmad Najafi Abrandabadi; Seyedeh Mahsa Sheikh-; Narges Panahandeh (Tehran University of Medical Sciences, 2016)
Objectives: The aim of this in-vitro study was to assess the thermal effect of light emitting diode (LED) light curing unit on the enamel etching time. Materials and Methods: Three treatment groups with 15 enamel specimens each were used in this study: G1: Fifteen seconds of etching, G2: Five seconds of etching, G3: Five seconds of etching plus LED light irradiation (simultaneously). The micro shear bond strength (µSBS) of composite resin to enamel was measured. Results: The mean µSBS values ± standard deviation were 51.28±2.35, 40.47±2.75 and 50.00±2.59 MPa in groups 1, 2 and 3, respectively. There was a significant difference between groups 1 and 2 (P=0.013) and between groups 2 and 3 (P=0.032) in this respect, while there was no difference between groups 1 and 3 (P=0.932). Conclusion: Simultaneous application of phosphoric acid gel over enamel surface and light irradiation using a LED light curing unit decreased enamel etching time to five seconds without compromising the µSBS.